Correlation of Body Mass Index and Menstrual Length to Hemoglobin Levels in Adolescent Women - Mustika Sari, Yesi; Amelia, Amraini (KHD-Production, 2024)
Anemia is a condition in which the body experiences a lack of hemoglobin levels in the blood. In Indonesia, those who experience anemia the most are teenagers with a prevalence of 30-55%, meanwhile the proportion of anemia in women is higher than in men with a prevalence of 23.9%. Anemia in teenagers increases pregnant women's risk of chronic energy deficiency, stunting, low birth weight and other health problems. Body mass index (BMI) as an indicator of nutritional status and duration of menstruation is one of the factors causing anemia in adolescent girls, so this research aims to determine the relationship between BMI and duration of menstruation on hemoglobin levels in adolescent girls. Method: The research used a quasi-experimental design using the Nonequivalent Control Group Design model by selecting 60 young women who met the inclusion criteria as a sample. Results: Pearson correlation analysis shows that BMI is not correlated with hemoglobin levels with a p-value of 0.717, while the length of menstruation is correlated with hemoglobin levels in adolescent girls with the strength of the relationship being sufficient with an r-0.331 p-value of 0.010, which means that the longer the adolescent girls menstruate, the longer they menstruate. the lower the hemoglobin level.